Perancangan Sistem Informasi Promosi Berbasis Web - Rometdo Muzawi; Yoyon Efendi (JOISIE (Journal Of Information Systems And Informatics Engineering), 2017)
Increasing technological developments are marked by the many innovative new technological discoveries produced by big companies with increasingly keen competition in meeting their customers' needs. SMA Negeri 1 Sawahlunto is one of the favorite educational institutions in Sawahlunto. As we know that now every institution / educational institutions vying in the delivery of information and promotion in various ways, such as through electronic media, newspapers, and others. One form of electronic media promotion that utilizes the science of technology is by displaying information or promotion based on the website. Publication of information and promotion through an online site SMA Negeri 1 Sawahlunto, will provide effectiveness and efficiency for people who want to get school information without having to come directly to SMA Negeri 1 Sawahlunto.With the development of web-based information systems, is expected to produce a quality system in the delivery of information and promotion at SMA Negeri 1 sawahlunto.